2011
DOI: 10.1038/emboj.2011.378
|View full text |Cite
|
Sign up to set email alerts
|

The human microcephaly protein STIL interacts with CPAP and is required for procentriole formation

Abstract: Centriole duplication involves the growth of a procentriole next to the parental centriole. Mutations in STIL and CPAP/CENPJ cause primary microcephaly (MCPH). Here, we show that human STIL has an asymmetric localization to the daughter centriole and is required for procentriole formation. STIL levels oscillate during the cell cycle. Interestingly, STIL interacts directly with CPAP and forms a complex with hSAS6. A natural mutation of CPAP (E1235V) that causes MCPH in humans leads to significantly lower bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
304
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(330 citation statements)
references
References 45 publications
16
304
1
1
Order By: Relevance
“…Similarly, the number of Sas‐6 molecules at centrosomes rose from ~346 in G1/S arrested cells to 440 in G2/M cells (Fig 5B) and those of STIL from 167 to 318 (Fig 5C). Neither Sas‐6‐EGFP nor STIL‐EGFP could be detected at centrosomes in mitotic cells (Fig 5B and C), consistent with ubiquitin‐dependent proteolytic degradation of both proteins (Strnad et al , 2007; Tang et al , 2011a; Arquint et al , 2012; Vulprecht et al , 2012; Arquint & Nigg, 2014). …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Similarly, the number of Sas‐6 molecules at centrosomes rose from ~346 in G1/S arrested cells to 440 in G2/M cells (Fig 5B) and those of STIL from 167 to 318 (Fig 5C). Neither Sas‐6‐EGFP nor STIL‐EGFP could be detected at centrosomes in mitotic cells (Fig 5B and C), consistent with ubiquitin‐dependent proteolytic degradation of both proteins (Strnad et al , 2007; Tang et al , 2011a; Arquint et al , 2012; Vulprecht et al , 2012; Arquint & Nigg, 2014). …”
Section: Resultssupporting
confidence: 69%
“…Sas‐6 is a major component of the cartwheel and contributes to confer ninefold symmetry (van Breugel et al , 2011; Kitagawa et al , 2011; Guichard et al , 2013; Fong et al , 2014; Wang et al , 2015). The protein CPAP gets recruited to promote the assembly of microtubules onto the cartwheel (Tang et al , 2011a; Cottee et al , 2013; Sharma et al , 2016), and this step is likely assisted by Cep135 (the human homolog of Chlamydomonas Bld10) (Hirono, 2014). CPAP also cooperates with additional proteins, including CP110, in determining the length of nascent centrioles (Kohlmaier et al , 2009; Schmidt et al , 2009; Tang et al , 2009; Comartin et al , 2013; Lin et al , 2013; Sharma et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although several centriolar proteins such as STIL, SAS-6, CEP120, SPICE1, and CEP135 can interact with CPAP and positively regulate the centriole duplication and elongation process (30,32,45,46), this is the first study that uncovers the mechanism by which CPAP levels are regulated in the cell to restrict the centriole length. Earlier we showed that centrobin binds to CPAP directly, and this interaction is essential for maintaining CPAP levels on centrioles (48).…”
Section: Discussionmentioning
confidence: 99%
“…The duplication process involves three stages: initiation, elongation, and maturation. Initiation process includes the recruitment of essential centriolar proteins such as CEP152, PLK4, hSAS-6, STIL, CPAP 2 , CEP135, CP110, ␥-tubulin, and centrobin to the proximal end of preexisting mother centrioles (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Once this pro-centriolar protein complex is formed, centrioles are elongated to achieve a maximum length of ϳ500 nm and width of ϳ200 nm by the addition of ␣/␤-tubulin heterodimers onto it (37).…”
mentioning
confidence: 99%
“…Strikingly, four of these carry MCPH-linked mutations [26][27][28]. CPAP/ MCPH6 appears to be a key node of the MCPH protein network, because it binds STIL/MCPH7, CEP152/MCPH9 and CEP135/MCPH8, although probably not simultaneously [29][30][31][32]. A missense MCPH mutation weakens the ability of CPAP to bind STIL and impairs centriole production [32][33][34][35].…”
Section: Centrosomes In Brain Developmentmentioning
confidence: 99%